Innovation in the Production Process Oriented towards SDG 9 in the Company Trujillo Pan - Suarez Torres, Betty Lizby; Asto Galarreta, Kenya Tatiana; Alejandro Heredia, Luciana Pamela; Carranza Escobedo, Pedro; Apaestegui Goicochea, Andrea Gianina (LACCEI, 2025)
The international rise of key inputs and the low technological density in the Peruvian bakery pose structural challenges to be addressed through the alignment with the sustainable development goal SDG 9. Therefore, the objective of this study proposes a model for improving the production process in the Trujillo Pan company with a focus on SDG 9 through the application of the Business Process Management (BPM) methodology, which began with the diagnosis of the AS-IS process that showed operational failures, reprocesses and low traceability; In response to the problem, two TO-BE proposals were addressed, including an infrastructure and digital innovation, considering the implementation of the Trujipro ERP system that allows the automation of critical tasks with artificial intelligence, in addition, Six Sigma was integrated for the efficient management of incidents, Lean Management (Kaizen) for the creation of continuous improvement reports by production branch, including shrinkage reports. In the same way, KPIs were formulated to evaluate the performance of the process; thus, the results of the simulation of the two proposals showed a decrease of 30.18 % in execution time and 79.80 % in operating costs